Family Dynamics and the Developing Child: The Influence of Parenting Behaviours and Family Functioning on Self-Harm and Suicidality in Childhood and Adolescence - Hammond, Nicole Grace (Université d'Ottawa / University of Ottawa, 2025)
Adolescent self-harm is a global public health problem. Suicide is a leading cause of death among adolescents aged 15-19 years, and self-harming thoughts and behaviours are risk factors for suicide. The family environment and associated experiences are recognized as a social determinant of health, affecting the developing child in a myriad of ways, including their mental health. Family dynamics directly teach the child how they must adapt and interact with the world. Ultimately, how a family functions and the parenting practices they rely on influence the child's socioemotional development. What is not understood is whether family dynamics confer prospective risk or protective effects on the onset of self-harming thoughts and behaviours in childhood and adolescence. Similarly, it is unclear whether these risk or protective effects are causal. Among adolescents who develop self-harming thoughts or behaviours, many do not seek support, not at least until professional mental health care may be urgently required. It has yet to be determined whether family dynamics may promote or hinder support-seeking behaviours among adolescents who experience self-harming thoughts or behaviours. The overall objective of this body of doctoral work was to address these key knowledge gaps to inform clinical practice and, more long-term, upstream suicide prevention efforts. By summarizing the prospective literature base (study 1), we found that negative family dynamics of family dysfunction and negative parenting practices longitudinally predict self-harm and suicidality (suicidal ideation and attempt) in childhood and adolescence. In study 2, we employed causal inference methods (i.e., marginal structural models) to estimate the effect of negative parenting practices (harsh and withdrawal methods) on self-harm in adolescence. Both forms of negative parenting practices led to the onset and maintenance of non-suicidal self-harm in adolescence. In the last study (study 3), we demonstrated that cross-sectionally and among adolescents experiencing suicidal ideation, negative family dynamics are a barrier to help-seeking from family and may lead the adolescent to seek support elsewhere (i.e., online). The findings of this doctoral work highlight the importance of family dynamics on the mental health of the developing child. We provide several clinical and public health recommendations, including addressing family dynamics among children and adolescents presenting with self-harming thoughts or behaviours, and formally recognizing family dynamics as a risk and protective factor in suicide prevention efforts.
Keywords: parenting; family functioning; adolescence; childhood; self-harm; suicidality; population health; epidemiology